2019
DOI: 10.1111/iwj.13273
|View full text |Cite
|
Sign up to set email alerts
|

Closed incision negative pressure therapy following abdominoplasty after breast reconstruction with deep inferior epigastric perforator flaps

Abstract: Autologous breast reconstructions using deep inferior epigastric perforator (DIEP) flaps create a large incision, presenting an opportunity for surgical site complications. In this pilot study, we aimed to examine outcomes in DIEP donor site incisions managed with standard dressings (control; n = 5) or closed incision negative pressure therapy (ciNPT; n = 5). We observed no significant differences between group age, body mass index, and past medical history. Both treatment groups had a similar duration of hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
1
18
1
Order By: Relevance
“…The present study has some limitations. The number of patients was small, though still comparable to other similar studies in the literature [ 17 , 20 ]. This might lead to a type 2 statistical error, explaining the lack of statistical evidence for the effectiveness of CINPT in TMG flap breast reconstruction despite the observed differences between both study groups.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The present study has some limitations. The number of patients was small, though still comparable to other similar studies in the literature [ 17 , 20 ]. This might lead to a type 2 statistical error, explaining the lack of statistical evidence for the effectiveness of CINPT in TMG flap breast reconstruction despite the observed differences between both study groups.…”
Section: Discussionsupporting
confidence: 77%
“…The advantages of CINPT have been outlined in multiple studies in plastic and reconstructive surgery as well as in oncological breast surgery [ 13 , 14 , 15 , 16 ]. In particular, evidence exists for the superiority of CINPT compared to conventional wound management at the donor site of patients undergoing free flap breast reconstruction from the lower abdomen [ 17 , 18 , 19 , 20 ]. This is the first study to evaluate the use of CINPT on donor site healing and patient perception in TMG flap breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…For highly visible incisions, or those resulting from cosmetic procedures, scar appearance is also an important outcome. Improved scar appearance has been observed in incisions managed with ciNPT versus control dressings for abdominal flap donor sites, 70 abdominoplasty, 71 and breast surgery in high‐risk patients 52 . A recent systematic review identified a moderate level of evidence supporting the use of ciNPT to improve scarring characteristics 72 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings add to the body of literature on this topic. Several studies have shown promising results with ciNPT for general wound management [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Smolle et al demonstrated a reduction in wound complications in patients who received ciNPT for orthopaedic surgical sites (total joint arthroplasty) and colorectal laparotomy sites [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the largest study to our knowledge investigating the use of ciNPT for breast reconstruction abdominal donor sites. Fang et al retrospectively compared outcomes in 10 patients with abdominal free flap breast reconstructions (ciNPT = 5, non-ciNPT = 5), concluding that ciNPT dressings resulted in faster wound healing and better cosmesis; however, without statistical significance [ 16 ]. Muller-Sloof et al conducted a prospective randomised control trial of 51 patients (ciNPT = 25, non-ciNPT = 26) who underwent breast reconstruction with abdominal free flaps, comparing ciNPT (Prevena) with standard adhesive dressings, demonstrating a reduction in incidence of wound dehiscence in the ciNPT cohort [ 15 ].…”
Section: Discussionmentioning
confidence: 99%